A simplified strategy for molecular formula determination of chemical constituents in traditional Chinese medicines based on accurate mass, A + 1 and A + 2 isotopic peaks using Fourier transform ion cyclotron resonance mass spectrometry. (6th October 2020) - Xu, Lu; Zhang, Yu; Zhang, Qingyu; Wang, Xue; Chu, Xiaowen; Li, Xintong; Sui, Wenwen; Han, Fei
Abstract : Rationale: Recently, isotopic fine structures derived from Fourier transform ion cyclotron resonance mass spectrometry have been used to determine the molecular formula for unknown compounds in many complex systems. However, a simplified strategy for molecular formula determination of chemical constituents in traditional Chinese medicines (TCMs) based on accurate mass, A + 1 and A + 2 isotopic peaks is necessary. Methods: Salviae miltiorrhizae was selected as a representative species. First, the chemical constituents were chromatographically separated and their accurate masses were obtained. The A + 1 and A + 2 isotopic peaks of all chemical constituents were then also acquired. Finally, the chemical formulae of the chemical constituents were determined. Results: In the sample of Salviae miltiorrhizae, the formulae of 38 CHO‐containing chemical constituents were quickly determined, and all chemical constituents were identified using their tandem mass spectrometric data. Moreover, the method was validated by comparison of the A + 1 and A + 2 isotopic peaks, their fragmentation patterns and the retention times of six selected standard substances. Conclusions: The results demonstrate that the described strategy performs well for molecular formula determination of chemical constituents in TCMs. This also indicates that this method will be meaningful for the structural identification of chemical constituents of TCMs.